POTRET KEMISKINAN KAUM MARJINAL PADA NOVEL ORANGORANG BIASA KARYA ANDREA HIRATA (THE PORTRAIT OF MARGINAL PEOPLE’S POVERTY IN NOVEL ORANG-ORANG BIASA BY ANDREA HIRATA) - Eka Aprilina Hasibuan (Universitas Lambung Mangkurat, 2021)
Abstract The portrait of marginal people’s poverty in novel Orang-orang Biasa by Andrea Hirata. This study aimed to identify the issues this study aims to uncover social facts that were objectively reviewed by the authors about conflicting communities or often referred to as social inequalities. This study uses qualitative approach using deductive development by Mayring. Analyzed through the theory of literary sociology of George Lucas, who considers literature is a reflection in society. Reading and note-taking techniques were used in this research as techniques in collected the data. The data is the novel Orang-Orang Biasa by Andrea Hirata. Data collection techniques in this study were carried out by coding the data findings, analyzing the data in the study, and interpreting the data. The results found in the research show that there are three poverty portraits of marginalized people, which is a term from a small group and is usually marginalized people. The problems of poverty experienced by the marginalized related to one another, including education poverty, moral poverty and wealth poverty. Key words: sociology of literature, poverty portrait, marginal Abstrak Potret kemiskinan kaum marjinal pada novel orang-orang biasa karya Andrea Hirata. Penelitian ini berujuan untuk mengungkap fakta-fakta sosial yang diulas secara objektif oleh penulisnya tentang masyarakat yang penuh pertentangan atau sering disebut dengan kesenjangan sosial. Penelitian ini menggunakan pendekatan kualitatif menggunakan pengembangan deduktif oleh Mayring. Analisis melalui teori sosiologi sastra George Lucas yang menganggap sastra sebagi refleksi cerminan dalam masyarakat. Teknik baca dan catat merupakan teknik pengumpulan data yang digunakan dalam penelitan ini. Data berupa teks pada novel Orang-Orang Biasa karya Andrea Hirata. Teknik pengumpulan data dalam penelitian ini dilakukan dengan cara memberi pengkodean pada temuan data, menganalisis data dalam penelitian, dan menginterpretasikan data. Hasil penelitian yang ditemukan menunjukkan adanya data tentang tiga potret kemiskinan kaum marjinal yang merupakan istilah dari suatu kelompok yang kecil jumlahnya dan biasanya merupakan orang-orang yang terpinggirkan. Permasalahan kemiskinan yang dialami oleh kaum marjinal menimbulkan masalah yang saling berkaitan, diantaranya adalah kemiskinan pendidikan, kemiskinan moral dan kemiskinan harta.Kata-kata kunci: sosiologi sastra, potret kemiskinan, marjinal